The effect of dietary black cumin seeds (Nigella sativa L.) on the performance of broilers - Guler, T; Dalkiliç, B; Ertas, ON; Çiftçi, M (Asian-Australasian Assoc Animal Production Soc, 2006)
Three hundred and sixty sexed 3-day-old broiler chicks were divided randomly into six treatment groups (control, antibiotic and black cumin at four levels) of 60 birds each. Black cumin seeds at 0.5%, 1%, 2% or 3% and avilamycin at 10 mg/kgt were added to the basal diet and their effects determined on feed intake, daily live weight gain, feed conversion ratio and carcass characteristics. There were no significant differences in daily feed intake at 21 and 42 days (p > 0.05). Average daily gain was significantly different between the treatments. The birds fed the diet containing 1% black cumin seeds and antibiotic were the highest average daily gain, followed by those the other treatment diets and negative control (p < 0.05). From I to 42 days of age, feed conversion ratios were improved significantly by supplementation with 1% black cumin seeds and with antibiotic (p < 0.05) by approximately 5% compared to the control group. Similarly, the highest cold carcass, thigh, breast, wing, neck and liver weights were observed in the 1% black cumin and antibiotic groups (p < 0.05). Accordingly, 1% supplementation of black cumin seeds to diets could be considered as an alternative natural growth promoter for poultry, instead of antibiotics.
Keywords: black cumin seeds; antibiotic; broiler; performance